Respuesta :

Answer:

i just know x=3 and y=-1

Answer:

y = -1    x = 3

Explanation:

First you start by singling out either the x or y

2x + 3y= 3

-2x - 12y = 6

go top to down x to x and y to y and c to c

so you get:

0x + -9y = 9

Then just divide by the remaining amount

-9y = 9      ( divide -9 to nine to single y)

y = -1

Then you do the same for x

-4x - 6y = -6

x + 6y = -3

you get

-3x + 0y = -9

Now just single x and your done

-3x = -9   ( divide by -3 from both sides to single x out)

x = 3